Policy Recommendations for Promoting the Use of Artificial Intelligence Technology at Patumkongka School under the Secondary Educational Service Area Office Bangkok 2 - Promaukson, Patcharee; Thaima, Waraporn (Sripatum Review of Humanities and Social Sciences, 2026)
This research aimed to: 1) examine the priority needs for the use of artificial intelligence (AI) technology at Patumkongka School, and 2) develop policy recommendations to promote the use of artificial intelligence technology at Patumkongka School. The research employed an explanatory mixed methods research design. The population involved 64 teachers at Patumkongka School. The research instrument was a five-point Likert scale questionnaire. Data were analyzed using descriptive statistics, including percentages, means, and standard deviations. Priority needs were analyzed using the Modified Priority Needs Index (PNImodified). The qualitative phase involved five school administrators and teachers. Data were collected through group interviews and analyzed using content analysis. The findings revealed that: 1) the current state of artificial intelligence utilization by school administrators was at a moderate level, whereas the desired state was at the highest level. The aspect with the highest priority needs was the support of technological resources and infrastructure, followed by planning and policy, organizational culture, development of teachers’ and staff’s digital skills, and technological leadership, respectively. The results of this study led to the development of policy recommendations that can serve as practical guidelines for promoting the systematic and sustainable use of artificial intelligence technology in educational institutions. 2)The study proposed five policy recommendations dimensions, consisting of, Aspect 1. support for technological resources and infrastructure, Aspect 2. planning and policies to promote the use of artificial intelligence (AI) technology, Aspect 3. organizational culture that promotes the use of technology and innovation, Aspect 4. development of digital skills among teachers and school personnel, and Aspect 5. technological leadership of school administrators. Altogether, the five policy recommendations dimensions were synthesized into a total of 64 practices.